Attitude Realization in Tempo.co’s News Coverage of Bahlil Lahadalia’s Doctoral Program: An Appraisal Analysis - Namira Az-Zahra; T. Thyrhaya Zein; Muhammad Yusuf (Universitas Negeri Semarang, 2026)
News reporting does not merely convey facts but also realizes social evaluation through linguistics choices employed in news texts. This study analyzes the realization of attitude in the news coverage of Tempo.co concerning the controversy surrounding Bahlil Lahadalia’s doctoral program and to reveal how evaluative patterns represents the media’s stance toward the actors and intitutions involved in the debate over academic legitimacy. This research employs a qualitative descriptive approach using discourse analysis based on Appraisal Theory, paticulary the attitude subsystem comprising affect, judgement, and appreciation. The data consist of 282 evaluative clauses identified in 25 news articles published between October 16, 2024, and March 22, 2025. The findings show that judgement is the most dominant type of attitude, occurring in 218 clauses (77%), followed by appreciation (45 clauses; 16%) and affect (19 clauses; 7%). The dominance of judgement indicates that the news frames the issue as matter of compliance with academic norms, scientific integrity, and institutional accountability. Most evaluations are realized through inscribed attitude and attributed to external sources possessing symbolic authority. These findings suggest that evaluative language in Tempo’s reporting constructs a normative framework of academic legitimacy in the public sphere.